Tumour-activated liver stromal cells regulate myeloid-derived suppressor cells accumulation in the liver. (7th February 2017) - Zhang, H; He, G; Kong, Y; Chen, Y; Wang, B; Sun, X; Jia, B; Xie, X; Wang, X; Chen, D; Wei, L; Zhang, M; et al.
Summary: Regulating mechanisms underlying hepatic myeloid-derived suppressor cell (MDSC) accumulation remain to be described. Here, we provide evidence for the involvement of tumour-activated liver stromal cells in the process of hepatic MDSCs migration and accumulation. Our data showed an elevated frequency of MDSCs in the liver of tumour-bearing mice. Moreover, tumour-activated liver stromal cells promote MDSC migration into the liver site. Further investigation indicated higher levels of cytokine and chemokine expression in liver stromal cells after exposure to the tumour-conditioned supernatant. Notably, the expression levels of proinflammatory factors, mainly including macrophage colony stimulating factor (M-CSF), transforming growth factor-β (TGF-β), monocyte chemotactic protein-1 (MCP-1) and stromal-derived factor-1 (SDF-1), increased after treatment with tumour-conditioned supernatant, and blockade of MCP-1 or SDF-1 decreased the proportion of tumour infiltrated MDSCs in mice co-transplanted with liver stromal cells and tumour cells, but not in mice with only tumour cells injection. These findings demonstrate that tumour-activated liver stromal cells produce higher levels of chemokines and cytokines, which may contribute to MDSC accumulation into the liver site in patients with liver cancer. Graphical Abstract: